Doctoral students’ perceptions of written feedback and engagements markers on thesis proposals - Victor Danarajan, Sharon Sharmini; Yahya, Muhammad Yasir; Lee, Geok Imm; Ali Hussein, Zina (UK Zhende Publishing Group, 2024)
Writing a thesis proposal is an essential part of the doctoral students’ candidacy. The quality of feedback and the rhetorical resources conveyed in such feedback, especially engagement markers, can have a great impact on students’ perception and engagement with feedback. However, doctoral students’ perceptions towards types of feedback and engagement markers communicated by supervisors and peers on students’ research proposals is thin on the ground. Therefore, this study investigated the types of written feedback and engagement markers EFL and ESL students perceived as useful for their thesis proposal development. A quantitative method in the form of questionnaire was employed with 23 students at University Putra Malaysia. Results indicated that, though EFL and ESL students held quite consistent perceptions toward certain types of feedback and engagement markers, their prior experience, educational and cultural issues, and understandings seemed to shape their different perceptions and affect their receptivity and utilization of feedback. Results from this study offer useful guidelines on how to provide an effective and resourceful feedback to meet EFL and ESL students’ requirements and expectations in higher education.